Rocky Start of Dinosaur National Monument (USA), The World's First Dinosaur Geoconservation Site - Kenneth Carpenter (Geoconservation Research)
The quarry museum at Dinosaur National Monument, which straddles the border between the American states of Colorado and Utah, is the classic geoconservation site where visitors can see real dinosaur bones embedded in rock and protected from the weather by a concrete and glass structure. The site was found by the Carnegie Museum in August 1909 and became a geotourist site within days of its discovery. Within a decade, visitors from as far as New Zealand traveled the rough, deeply rutted, dirt roads to see dinosaur bones in the ground for themselves. Fearing that the site would be taken over by others, the Carnegie Museum twice attempted to take legal possession of the land. This had consequences far beyond what the Museum intended when the federal government declared the site as Dinosaur National Monument in 1915, thus taking ultimate control from the Carnegie Museum. Historical records and other archival data (correspondence, diaries, reports, newspapers, hand drawn maps, etc.) are used to show that the unfolding of events was anything but smooth. It was marked by misunderstanding, conflicting goals, impatience, covetousness, miscommunication, unrealistic expectation, intrigue, and some paranoia, which came together in unexpected ways for both the Carnegie Museum and the federal government.